Community Care : Policy and Practice - Means, Robin and Smith, Randall (Basingstoke Macmillan, 1994)
Community care in England and Wales is undergoing massive changes with social services departments taking the lead agency role in developing a mixed economy of social care and services. This book outlines and analyzes these reforms, linking them to the long history of service neglect.
Include References and Index
Keywords: Community health services